Reform, university autonomy and national interest: analysis of the chair of political economy at the National University of Colombia, Bogota 1933 - 1938 - Molina Bravo, José (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2014)
This paper presents an approach to the University Reform from a sociopolitical perspective. It describes the importance of the chairs and place that in the process of change is assigned to the processes of academic professional and intellectual development. It takes into account the case of the Ntional University of Colombia, in the chair of Political Economy, of the Faculty of Law and Political Science (1933 - 1938). The sources are taken from a file to characterize the atmosphere of reform, the discussions generated in the above-mentioned option and the way it has organized the teaching of political economy. In its analysis there are mixed approaches on the intellectual field - university, the social perspective of the phenomenon of education and critical discourse analysis.